Do Workers’ Remittances Promote Financial Development? - Aggarwal, Reena; Demirgüç-Kunt, Asli; Martinez Peria, Maria Soledad (World Bank, Washington, DC, 2012)
Workers' remittances to developing countries have become the second largest type of flows after foreign direct investment. The authors use data on workers' remittance flows to 99 developing countries from 1975-2003 to study the impact of remittances on financial sector development. In particular, they examine whether remittances contribute to increasing the aggregate level of deposits and credit intermediated by the local banking sector. This is an important question considering the extensive literature that has documented the growth-enhancing and poverty-reducing effects of financial development. The findings provide strong support for the notion that remittances promote financial development in developing countries.